2011
DOI: 10.5127/jep.014511
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Self-Focused Attention in Children with Social Anxiety Disorder and in Socially Anxious and Non-Anxious Children

Abstract: Cognitive behavioral models of social anxiety disorder (SAD) in adults suggest that self-focused attention maintains social anxiety. However, this hypothesis has not yet been tested in children. This study therefore examined self-focused attention in relation to social anxiety in children. Self-focused attention was experimentally varied (internal vs. external) in 20 children with SAD, 20 children with high social anxiety and 20 non-anxious controls while engaging in a performance task in front of two adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…First, many studies have found a strong relationship between social anxiety and trait SFA (see Bögels & Mansell, 2004, for a review). Research has consistently and convincingly demonstrated that clinically and non-clincially socially anxious adults display higher SFA in social situations relative to controls and compared to other phobias (see Bögels & Mansell, 2004; Hope, Gansler, & Heimberg, 1989; Spurr & Stopa, 2002 for reviews), and that these processes also occur among adolescents (Hodson, McManus, Clark, & Doll, 2008; Ranta, Tuomisto, Kaltiala-Heino, Rantanen, & Marrunen, 2014) and children (Higa & Daleiden, 2008; Kley, Tuschen-Caffier, & Heinrichs, 2011).…”
Section: Empirical Evidence For Self-focused Cognitive Processes In Smentioning
confidence: 99%
See 1 more Smart Citation
“…First, many studies have found a strong relationship between social anxiety and trait SFA (see Bögels & Mansell, 2004, for a review). Research has consistently and convincingly demonstrated that clinically and non-clincially socially anxious adults display higher SFA in social situations relative to controls and compared to other phobias (see Bögels & Mansell, 2004; Hope, Gansler, & Heimberg, 1989; Spurr & Stopa, 2002 for reviews), and that these processes also occur among adolescents (Hodson, McManus, Clark, & Doll, 2008; Ranta, Tuomisto, Kaltiala-Heino, Rantanen, & Marrunen, 2014) and children (Higa & Daleiden, 2008; Kley, Tuschen-Caffier, & Heinrichs, 2011).…”
Section: Empirical Evidence For Self-focused Cognitive Processes In Smentioning
confidence: 99%
“…Additional research investigating these processes among socially anxious children and adolescents would also be valuable, allowing for greater understanding of the development of self-focused cognitive processes across the lifespan. While there is preliminary evidence supporting the role of SFA (Higa & Daleiden, 2008; Hodson et al, 2008; Kley et al, 2011; Ranta et al, 2014) and PER (Schmitz et al, 2010; Schmitz et al, 2011) in socially anxious young people, no studies to date have investigated AR, and most research has employed analogue samples. Furthermore, it remains unclear whether the self-focused cognitive processes found among SAD individuals are transdiagnostic (e.g., Schmitz et al, 2011; McEvoy, Mahoney, & Moulds, 2010; Rood, Roelofs, Bögels, & Alloy, 2010) or specific to SAD and social threat (e.g., Abbott & Rapee, 2004; Fehm, Schneider, & Hoyer, 2007; Kocovski & Rector, 2007; Wong et al, 2015), and this issue this is worthy of further investigation.…”
Section: Summary and Future Researchmentioning
confidence: 99%
“…This calls into question the rationale for basic attentional bias training paradigms that simply train avoidance of negative stimuli. Second, the results presented by Kley et al (2011) suggest that attention retraining, in which children are taught how to direct their attention away from themselves in social situations, may be a useful addition to treatments for social phobia. Finally, Dodd et al (2011) andKramer et al (2011) both present evidence that socially phobic children have poor global social skills.…”
mentioning
confidence: 99%
“…For example, Miers et al (2011) showed that all children are poor at judging their physiological arousal. In addition, Kley et al (2011) showed that all children experienced increased anxiety when instructed to pay attention to their thoughts and feelings and Dodd et al (2011) showed that all children are more likely to underestimate their social skill when state anxiety is high. These findings therefore lead to questions regarding which factors are features of social phobia and which are normal processes experienced by all children under certain conditions, such as increased social anxiety or increased threat of negative evaluation.…”
mentioning
confidence: 99%
“…Kley, Tuschen-Caffir, and Heinrichs (2011) and Blote, Miers, Heyne, Clark & Westenberg (2014) present studies that support the idea that self-focused attention to inward aspects of self, increases anxiety by increasing negative self-image and decreasing social capability. This complex cognitive cycle seen in SAD has been observed in children and adolescents, eight years old and up (Kley et al, 2011;Bolt et al, 2014).…”
Section: Cognitive Factorsmentioning
confidence: 90%